2021
DOI: 10.3390/ijerph18083864
|View full text |Cite
|
Sign up to set email alerts
|

The Energy to Smoke: Examining the Longitudinal Association between Beverage Consumption and Smoking and Vaping Behaviours among Youth in the COMPASS Study

Abstract: This study examined the longitudinal association between changes in sugar-sweetened and/or caffeinated beverage consumption and smoking/vaping behaviour among Canadian adolescents. Using longitudinal data from the COMPASS study (2015/16 to 2017/18), four models were developed to investigate whether beverage consumption explained variability in smoking and vaping behaviour in adolescence: (1) smoking initiation, (2) vaping initiation, (3) current smoking status, and (4) current vaping status. Models were adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Conversely, a study with adolescent girls found an inverse longitudinal association between the tendency to consume processed or sweet high-fat foods and the tendency to drink alcohol (Cummings et al, 2017). Another study did not find an association between sugar-sweetened beverages and tobacco smoking (Fagan et al, 2021). It is necessary to consider that discrepancies between studies are possibly due to the characteristics of the samples studied (e.g., sample size, proportion of boys and girls, age range, socioeconomic and cultural aspects, etc.…”
Section: Comparison With the Available Evidencementioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, a study with adolescent girls found an inverse longitudinal association between the tendency to consume processed or sweet high-fat foods and the tendency to drink alcohol (Cummings et al, 2017). Another study did not find an association between sugar-sweetened beverages and tobacco smoking (Fagan et al, 2021). It is necessary to consider that discrepancies between studies are possibly due to the characteristics of the samples studied (e.g., sample size, proportion of boys and girls, age range, socioeconomic and cultural aspects, etc.…”
Section: Comparison With the Available Evidencementioning
confidence: 95%
“…Most of the evidence on the association between UPF and substance use is based on preclinical studies with animals (Witek et al, 2022), a few epidemiological studies with adults (Amadieu et al, 2021;Schulte et al, 2015) and adolescents (Cummings et al, 2020;M. Wang et al, 2017), mostly focusing on specific UPF such as soft drinks (Atorkey et al, 2021;Fagan et al, 2021;Pengpid & Peltzer, 2019;Shih et al, 2020;Terry-McElrath et al, 2014). Moreover, these studies reported mixed results, and it remains unclear whether and to what extent these behaviors (i.e., UPF consumption and the use of psychoactive substances) are associated among adolescents.…”
mentioning
confidence: 99%
“…Several study authors have reported the high correlation of smoking with physical inactivity, less intake of fruits and vegetables, or SSB drinking. 54,55 Binge drinking is also associated with physical inactivity and poor eating habits in adults. 50,56 On the basis of these findings, we suggest that smoking and binge drinking are essential unhealthy lifestyle behaviors that impact clustering and may significantly contribute to the manifestation of an co-occurrence with other unhealthy behaviors in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified that either smoking or binge drinking co-occurs with other behaviors of physical inactivity and poor eating (ie, low-fruit intake or SSB drinking). Several study authors have reported the high correlation of smoking with physical inactivity, less intake of fruits and vegetables, or SSB drinking 54,55 . Binge drinking is also associated with physical inactivity and poor eating habits in adults 50,56 .…”
Section: Discussionmentioning
confidence: 99%